Personality-Model and Creative life-orientation [Личность-эталон и жизнесозидающая креативность] (in Russian) - Иванченко, Андреянна Алексеевна; Ivanchenko, Andreyanna; Іванченко, Андреянна Олексіївна (Харків: ХНУВС, 2013)
The pattern of an individual’s life path is woven from interweaving of various lines that emerge during the person's formation and development. Each milestone in life is filled with emotional-sensual overtones and the information core, namely they form an individual experience. But life experience (both of a child and an adult) is not just information-filled memory cells, it is the result of a person’s reflection on the structural content of his life, which condenses in the form of emotionally-cognitive clots and images. Узор жизненного пути индивида соткан из переплетения различных линий, которые вырисовываются по ходу становления и развития человека. Каждая жизненная веха наполнена эмоционально-чувственными подтекстом и информационным ядром, а именно они и формируют индивидуальный опыт. Но жизненный опыт (как ребенка, так и взрослого) – это не просто информационно наполненные ячейки памяти, это результат рефлексии человека о структурной содержательности жизни, который конденсируется в виде эмоционально-когнитивных сгустков и образов.
Иванченко А.А., кандидат психологических наук, доцент Харьковский национальный университет имени В.Н.°Каразина.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology; креативность; личность-эталон